A state-of-the-art review of solar air-conditioning systems. (July 2016) - Nkwetta, Dan Nchelatebe; Sandercock, Jim
Abstract: To reduce greenhouse gas emission, solar cooling is an attractive and environmentally friendly application since there is a direct match with cooling demand and peak incident solar radiation. In addition, solar absorption refrigeration technologies are regarded as a promising way to meet the growing refrigeration needs related to thermal comfort, vaccines, conservation of foods and medicines as well as crop drying. Presently, two systems in common used are, the single and double effects absorption chillers with the difference between the two systems being the operating temperature range. This comprehensive review looks at the available methods (theoretical modeling/simulation and experimental) that have been used for the powering of single and double effects solar absorption chillers, other solar cooling systems and their merits, system integration, design optimization and cost effectiveness of each system. Furthermore, solar collector׳s area and efficiency needed for each load profile is reviewed. Higher temperature differential generated by concentrated augmented solar collectors appears to be economically viable for solar cooling systems, as peak incident solar radiations are a direct coincidence with peak solar cooling needs. Research has demonstrated that the use of evacuated tube and concentrated augmented solar collectors helps to improve the coefficient of performance of single and double-effect lithium bromide–water (LiBr/H2 O) absorption chillers. However, there is still the need for more research on system integration and optimization of concentrated augmented solar collectors powering single and double-effect lithium bromide–water (LiBr/H2 O) absorption chillers with thermal energy storage.